PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 9 BURU - Siami Prafitriani; M. Chairul Basrun Umanailo; Nanik Indrayani; Syafa Lisaholit; Dina Chamidah (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine whether there is a positive influence between emotional intelligence on mathematics learning achievement of Grade VII students of SMP Negeri 9 Buru. This research is an ex-post facto research. The subjects in this study were grade VII students at SMP Negeri 9 Buru, totaling 100 students out of 135 students. Data collection techniques using observation techniques, questionnaires and study documentation. The results of the study stated that there was a positive and significant influence between emotional intelligence on mathematics learning achievement of Grade VII students of SMP Negeri 9 Buru. These results mean that the higher the level of emotional intelligence, the higher the mathematics learning achievement obtained by students. Conversely, the lower the level of emotional intelligence, the lower the mathematics learning achievement obtained by students.